Bendiocarbamate toxicity in the chick embryo - Petrovová, Eva; Sedmera, David; Míšek, Ivan; Lešník, František; Luptáková, L (Folia biologica (Praha), 2009)
Carbamate pesticides generally possess low toxicity for warm-blooded vertebrates, but developmental data are scarce. We have therefore evaluated embryotoxicity of choline esterase inhibitor bendiocarbamate in the chick embryo. The pesticide was dissolved in 5% acetone in distilled water and a volume of 200 µl was administered over the embryo through membrana papyracea on embryonic days 2, 3, 4, 5, and 10. Sampling was performed on embryonic day 10, while the embryos treated on embryonic day 10 were sampled on embryonic day 17. The toxicity of bendiocarbamate was fairly low, and LD50 decreased with advancing development from 1 mg/ embryo on embryonic day 2 to 29 mg on embryonic day 5. Malformations in surviving embryos were observed rarely (< 3 %) and occurred in both control and experimental groups. There was a mild but statistically significant dose-dependent reduction in body weight, most pronounced in the treatment on embryonic days 5 and 10, but the maximum difference from controls was below 15 %. A small but not significant increase in the number of positive cells was observed in the eye, limb buds, and the central nervous system of embryos treated on embryonic days 3 and 4 and examined after supravital wholemount staining with Lysotracker Red for apoptosis. In agreement with previously published studies in other vertebrate animals, we conclude that bendiocarbamate does not possess significant toxicity in the avian embryo.
Keywords: Pesticides; pesticidy; Financing, Organized; Embryo, Nonmammalian; financování organizované; embryo nesavčí; Carbamates; zvířata; kuřecí embryo; Animals; karbamáty; Chick Embryo